A Fiber Bragg Grating Pressure Sensor and Its Application to Pipeline Leakage Detection. (26th June 2013) - Huang, Jun; Zhou, Zude; Zhang, Dongsheng; Wei, Qin
Abstract : The fiber Bragg grating (FBG) technology has been rapidly applied in the sensing technology field. In this paper, an FBG pressure sensor is designed and implemented to detect the leakage of prestressed concrete cylinder pipe (PCCP). The pressure sensor is mainly based on a Bourdon tube with two FBGs bonded on its outside and inside surfaces, respectively. The measurement principle and simulation analysis results are described. The wavelength shift difference of the two FBGs is utilized as a pressure sensing signal, the sensitivity is enhanced, and the temperature cross-sensitivity is compensated. Experimental results indicate that the measurement sensitivity is 1.414 pm/kPa in a range from 0 to 1 MPa, and the correlative coefficient reaches 99.949%. This kind of pressure sensor is effective to quasi-distributed measure and online monitor pressure of gas or liquid in industry and manufacture fields.